2018
DOI: 10.1158/1078-0432.ccr-17-3369
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Based Detection of EGFR T790M in Plasma from Non–Small Cell Lung Cancer Patients

Abstract: Tumor tissue biopsies carry risks and are not always possible, making liquid biopsies an attractive way to acquire molecular information from cancer patients. The EGFR T790M mutation is a critical biomarker in non-small cell lung cancer and has introduced new challenges in how these patients are managed. With the approval of osimertinib for patients failing first generation EGFR inhibitor therapy, the use of a liquid biopsy to detect EGFR T790M would reduce the number of unnecessary repeat biopsies. Detection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(139 citation statements)
references
References 37 publications
3
135
0
1
Order By: Relevance
“…Therefore, liquid biopsy is greatly explored in current oncology research due to its minimally invasive approach for early cancer detection and for responses to cancer treatment. 3,12 Circulating or cf-miRNAs disseminate from tumor tissue into the peripheral circulation 1 and are present in all body fluids, including whole blood, plasma, serum, sputum, saliva, urine, and cerebrospinal fluids. 2,13 These miRNAs are stable under harsh conditions, such as extreme pH, temperature, multiple freeze-thaw cycles, long-term storage, and even against RNase degradation.…”
mentioning
confidence: 99%
“…Therefore, liquid biopsy is greatly explored in current oncology research due to its minimally invasive approach for early cancer detection and for responses to cancer treatment. 3,12 Circulating or cf-miRNAs disseminate from tumor tissue into the peripheral circulation 1 and are present in all body fluids, including whole blood, plasma, serum, sputum, saliva, urine, and cerebrospinal fluids. 2,13 These miRNAs are stable under harsh conditions, such as extreme pH, temperature, multiple freeze-thaw cycles, long-term storage, and even against RNase degradation.…”
mentioning
confidence: 99%
“…These findings highlight the potential use of TEX diagnostic biomarkers for HNSCC [81,82]. Indeed, such TEX-based biomarkers as liquid biopsy diagnostics from Exosome Diagnostics were recently approved for clinical use for prostate and lung cancer [83,84]. These diagnostics aid clinicians in detecting, diagnosing, and monitoring cancer progression in addition to identifying the unique genetic composition of each patient's tumor.…”
Section: Tumor-derived Exosomesmentioning
confidence: 99%
“…Hence, analysis of tumor-derived EVs has emerged as an alternative approach to ctDNA to evaluate therapeutic effect of targeted therapy. Specifically, it has been reported that exosomal RNA can be a useful biomarker for detecting development of the T790M and other activating EGFR mutations, increasing sensitivity and specificity of traditional ctDNA analysis [89,90]. The importance of tumor EVs as clinical biomarkers is supported by the fact that EVs are directly implicated in the propagation of resistance mechanisms between cancer cells.…”
Section: Involvement Of Extracellular Vesicles In Resistance To Targementioning
confidence: 99%